The impact of socioeconomic factors on the efficiency of voluntary toxoplasmosis screening during pregnancy: a population-based study. Issue 1 (December 2016) - Lange, A.; Thyrian, J.; Wetzka, S.; Flessa, S.; Hoffmann, W.; Zygmunt, M.; Fusch, C.; Lode, H.; Heckmann, M.
Abstract Background Congenital toxoplasmosis is associated with severe complications. German state health insurance covers rubella, but not toxoplasmosis, immunity screening. We analysed the effect of socioeconomic factors on the efficiency of private toxoplasmosis screening during pregnancy. Methods Toxoplasmosis and rubella screening data (n  = 5402 mothers) were collected within the population-based Survey of Neonates in Pomerania (SNiP). Results At the first-trimester screening, 34.4 % (88.1 %) of expecting mothers were immune to toxoplasmosis (rubella). Susceptibility for toxoplasmosis (rubella) was observed in 39.6 % (8.9 %) and 25.8 % (2.95 %) were not tested. Data on a 2nd screening were available in a subgroup of women with negative immunity showing less than 45 % participation rate. Active toxoplasmosis (no rubella) infection was observed in 0.3 % (n  = 17) of pregnant women. A multiple logistic regression model (AIC = 719.67; AUC = 0.725) revealed that the likelihood of participating in a second toxoplasmosis screening increased among women with a good level of education and a steady partnership and decreased with paternal unemployment and the absence of breastfeeding. The highest probability of non-participation in toxoplasmosis screening was found among women with temporal burden and family responsibilities. A cost-benefit analysis showed that covering general screening for toxoplasmosis with health insurance saved costs. Conclusion Toxoplasmosis carried a substantial risk of infection during pregnancy. Although increased socioeconomic status was positively associated with the participation in toxoplasmosis screening, this was not the case when pregnant women had strong temporal burden and family responsibilities. This data supports the need for toxoplasmosis screening among pregnant women as a general healthcare benefit covered by insurance.